Aplikasi Akuntansi Penerimaan Dan Pengeluaran Kas Pada PT Kinarya Gemilang Adhitama Menggunakan Model Waterfall - Tika Susilawati; Syarif Hidayatulloh (Computer Science (CO-SCIENCE), 2023)
PT Kinarya Gemilang Adhitama manages cash receipts and disbursements using Microsoft Excel by recapitulating or calculating one by one transactions in the form of notes into financial reports. The cash management process tends to take a long time, and allows for a considerable risk of data redundancy and the quality of data and information to become inaccurate. Utilizing technology by building a cash receipts and disbursement application with the aim of developing and improving existing systems. By building a financial management application, it is hoped that it can help with the process of managing cash receipts and disbursements at PT Kinarya Gemilang Adhitama to become more efficient and effective. The software development method used in building the application is the SDLC method with the Waterfall model. The application is built with an automatic and unique cash number system so that it can reduce the risk of data redundancy. Furthermore, the application will be tested with Black Box which focuses on software in terms of logic and functionality which is carried out on the 4 main features of the application. The test results show valid results, which means that the application function is in accordance with the design.